Association of Baseline Neutrophil-to-Lymphocyte Ratio with Clinicopathological Characteristics of Papillary Thyroid Carcinoma. (9th May 2017) - Manatakis, Dimitrios K.; Tseleni-Balafouta, Sofia; Balalis, Dimitrios; Soulou, Vasiliki N.; Korkolis, Dimitrios P.; Sakorafas, George H.; Plataniotis, Georgios; Gontikakis, Emmanouil
Abstract : Objective . To investigate the potential association of neutrophil-to-lymphocyte ratio (NLR), a surrogate systemic inflammatory biomarker, with clinical and pathological characteristics of papillary thyroid cancers. Methods . 205 patients with papillary carcinoma were identified from the institutional thyroid cancer database between 2006 and 2015 (55 males, 150 females, mean age 51.2 ± 14.7 years). NLR was calculated as the absolute neutrophil count divided by the absolute lymphocyte count, based on the preoperative complete blood cell counts. Results . NLR was significantly higher in carcinomas with extrathyroidal invasion (2.74 ± 01.24 versus 2.39 ± 0.96, p = 0.04 ) and bilateral (2.67 ± 1.15 versus 2.35 ± 0.96, p = 0.03 ) and multifocal tumours (2.65 ± 1.08 versus 2.29 ± 0.96, p = 0.01 ), as well as lymph node-positive tumours (3.12 ± 1.07 versus 2.41 ± 1.02, p = 0.03 ). On the other hand, NLR values were not associated with gender, age, tumour size, histologic subtype, the presence of thyroiditis, and TNM staging. Conclusions . As an index of inflammation, NLR is inexpensive, readily available, and easy to extract from routine blood tests. We found increased NLR values in papillary carcinomas with poorer histopathological profile and more aggressive clinical behaviour. Whether this systemic inflammatory response, as expressed by the NLR, represents the inflammatory microenvironment leading to tumourigenesis, or is a tumour-associated phenomenon, remains to be elucidated and warrants further study.